Insights from tyrosinase into the impacts of modified morphology of calcium carbonate on the nacre formation of pearl oysters - Xiong, Xinwei; Cao, Yanfei; Li, Zhixin; Huang, Ronglian; Jiao, Yu; Zhao, Liqiang; Du, Xiaodong; Zheng, Zhe (Frontiers in Marine Science, 2022)
Tyrosinase is a type-3 copper protein with six conserved histidine residues within the copper-binding sites. It participates in mollusk nacre formation. Here, we identified nacreous-layer-specific tyrosinases (NLSTyr) from Pinctada fucata martensii (PmTyr-4 and PmTyr-6), as well as their homologs in Pinctada maxima (PmaxTyr and PmaxTyr4) and Pinctada margaritifera (PmarTyr and PmarTyr-4), which encoded tyrosinases without the six conserved histidine residues within the copper-binding sites. PmTyr-4 and PmTyr-6 mRNAs were spatially concentrated in the mantle central and pearl sac, which are the organs responsible for nacre formation. During shell regeneration and pearl formation, PmTyr-4 and PmTyr-6 were also significantly highly expressed in the mantle and pearl sac. RNA interference showed that PmTyr-4 participated in nacreous-layer formation. The recombinant protein of PmTyr-4 (rPmTyr-4) inhibited the calcium carbonate precipitation rate. Correspondingly, calcium carbonate crystallization assay showed that the aragonite crystals of the rPmTyr-4 group were smaller than those of the control group. Moreover, the calcite and aragonite morphologies of the rPmTyr-4 group were modified compared with the control group. These results suggested that NLSTyr in pearl oyster inhibited calcium carbonate precipitation and affected crystal morphologies during nacre formation. Our findings provided new insights into the evolution and function gain of tyrosinase in Mollusk.